(untitled) (Sebha University Conference Proceedings, 2024)
This study aims to design a website that provides guidelines and tests for students to obtain appropriate guidance for them in applying to the university stage. This study was conducted in secondary schools in the Traghen region during the academic year (2023). The study sample consisted of 60 students, and the research was followed in this study The quasi-experimental and descriptive analytical approaches were designed, where a website was designed that provides directions and consultations to students, and the research tools were the academic and cognitive achievement test and the skill performance test for the students, and the questionnaire card was designed as a tool for studying and using the Statistical Packages Program (S.P.S.S) to analyses the data to know the extent of their acceptance. In using these guidance sites that provide guidance to students in university majors, then in this stage, we analyses and determine the requirements that are used in building the site. A guidance website has been designed for high school students, which presents a set of questions according to the specialization that I studied in the high school stage and based on the results of the stage. High school grades, average grades obtained in previous academic courses, and the student’s academic and cognitive achievement Guidance and suggestions are given regarding the specialization appropriate to him and appropriate to his academic ability through the electronic guide on the website, and the results are indicated with statistically significant differences at the level of significance (a = 0.05) In the early test for choosing a university major, the study concluded by highlighting the most important recommendations and proposals through which the desired benefit can be achieved from using the electronic website in obtaining consultations and advice in the stage of directing students to